2014
DOI: 10.1116/1.4865896
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of silicon nitride for CMOS gate spacer technology. II. Impact of subsilicon surface carbon implantation on epitaxial regrowth

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It has been reported that the Si-C bonds are generated on the SiN surface during conventional RIE, 82) as well as on the Si surface. [83][84][85] Thus, the MD simulation results are qualitatively consistent with the earlier RIE experimental results, indicating that residual C atoms are firmly bonded with surface atoms after the desorption step. Because the Si-C bond energy is similar to the Si-N bond energy and a single C atom typically has four bonds to be connected with surface atoms, removing residual C atoms by Ar + ion bombardment requires the incident ion energy to be high enough to sputter SiN.…”
Section: Resultssupporting
confidence: 87%
“…It has been reported that the Si-C bonds are generated on the SiN surface during conventional RIE, 82) as well as on the Si surface. [83][84][85] Thus, the MD simulation results are qualitatively consistent with the earlier RIE experimental results, indicating that residual C atoms are firmly bonded with surface atoms after the desorption step. Because the Si-C bond energy is similar to the Si-N bond energy and a single C atom typically has four bonds to be connected with surface atoms, removing residual C atoms by Ar + ion bombardment requires the incident ion energy to be high enough to sputter SiN.…”
Section: Resultssupporting
confidence: 87%
“…Another possible reason is that Si-C bonds are formed on the surface. [27][28][29] As the binding energy of Si-C in the C (1s) photoemission (283.0 eV) is close to the peak position of a strong C-C (284.8 eV) bond, it was difficult to deconvolute the effect of Si-C. As Si-C is generated in the interface between HFC polymer and underlying SiN, the signal of Si-C seems to be under the detectable-level since the upper HFC polymer suppressed the photoelectron from the interface. Further study will be performed related to the Si-C bond by using other techniques.…”
Section: Analysis Of Etch-stop Mechanismmentioning
confidence: 99%
“…In conventional reactive ion etch (RIE) process, to obtain the desired mask selectivity, profile and CDs, fluorocarbon (FC) or hydro fluorocarbon (HFC) films are generated at the surface of a material, which act as a passivation layer for etch protection. [1][2][3][4][5][6][7][8][9][10] On the etch of Si 3 N 4 , as an example, high selectivity over Si up to 20 can be achieved by a carbon rich passivation layer made on top of the Si substrate. 11) However, such a deposition of the FC and HFC films frequently causes the clogging and etch stop issue during the process when the CD size becomes small.…”
Section: Introductionmentioning
confidence: 99%